Reaching global warming targets under ice-free arctic summers requires zero emissions by 2045. (Research'eu results magazine)
Ice-albedo feedback as a result of sea-ice melting, notably in the Arctic, is known to reinforce global warming. What is less known, however, is the impact of a no-summer ice scenario on the world's ambition to maintain global warming below 2 degree celcius by 2100. A study conducted under the TRANSRISK project paints a rather dark picture, highlighting the need to better understand the impact of rapid climate change in the region.